Effects of media length on biofilms and nitrification in moving bed biofilm reactors - Kody A. Garcia; Patrick McLee; Andrew J. Schuler (Biofilm, 2022)
Biofilms grown on free-floating plastic media are increasingly being used to cultivate biofilms in integrated fixed film activated sludge (IFAS) and moving bed bioreactor (MBBR) systems for wastewater treatment with the common goal of increasing nitrogen removal. Fundamental principles of fluid dynamics dictate that the length of internal media channels affects fluid velocities and shear forces across biofilm surfaces, which in turn should affect rates of mass transfer and biofilm growth and activity, but little is known about media length effects on water quality and biofilm characteristics. It was hypothesized that length affects biofilm thickness, microbial populations and their activities, and system performance. Nitrification rates and biofilm characteristics were monitored in parallel continuous flow, bench-scale MBBRs systems with media length as a controlled variable. Longer media produced biofilms with approximately twice the thickness and twice the mass per unit area than did media with one-third their length. Based on calculated head losses, the combined effects of length and constriction of internal channels led to an estimated 77% reduction in fluid velocity through the longer media relative to the shorter media. Longer media demonstrated more rapid development of nitrite oxidizing bacteria (NOB) activity than the shorter media over much of the study, as indicated by measurements of nitrite and nitrate, but AOB activity was similar in the two media. Both biomass and NOB activity were concentrated toward media ends, while ammonia oxidizing bacteria (AOB) activity was uniformly distributed across the media, based on testing of sectioned media. 16s rRNA amplicon sequencing indicated the presence of several putative heterotrophic nitrifying families, particularly Xanthomonadaceae, Comamonadadeae and Microbacteriaceae, as well as the autotrophic Bradyrhizobiacea (which includes the NOB Nitrobacter) were common on both media throughout the study. The short media enriched for Nitrosomonadaceae, which includes the AOB genus Nitrosomonas, while minimal autotrophic AOBs were found in the long media biofilm. These results provide insights to the design of media for improved performance, particularly with respect to nitrite versus nitrate production, which may be useful to improve nitrification and for energy saving processes for nitrogen removal such as deammonification. The research also provides fundamental insights regarding the effects of media geometry on biofilm structure and function, which advances our understanding of environmental factors affecting biofilm development.